Analisis Transformasi Halal Awerness dan Teknologi Blockchain Terhadap Penguatan Halal Value Chain Di Indonesia - Effendi, Kharisya Ayu; Mukhlis, Tanti Irawati; Padmanegara, Oliver Hasan; Widajatun, Vincentia Wahju (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to see whether Halal Awernes can influence the strengthening of the Halal Value Chain, also to see whether Blockchain Technology can affect the strengthening of the Halal Value Chain. This research method uses a quantitative method that proves the theory or results of previous research. The data used are SMEs in Indonesia, with a random sampling method using the formula according to (HOSMER et al., 1997). So that the obtained data that must be taken amounted to 96 respondents throughout Indonesia. Data analysis uses SPSS 26. The results of this study are Halal Awerness and Blockchain Technology have a positive and significant effect on the Halal Value Chain. This means that, the higher the halal awerness of MSMEs towards halal products will further strengthen the implementation of the Halal Value Chain in Indonesia. The higher understanding and use of blockchain technology in MSMEs will further strengthen the implementation of the Halal Value Chain in Indonesia.